The novel IDO-1 inhibitor 3-047 combined with icaritin ameliorates neuroinflammation and diabetes-associated cognitive dysfunction with suppression of TLR4/MyD88/NF-κB signaling - Mo, Tingmei; Zhuang, Xia; Zhao, Wenxue; Wang, Baohua; Wang, Yuting; Ji, Wenjie; Liu, Dongguang; Zhang, Guimin; Yao, Ru; Xu, Yan; Yao, Jingchun (Frontiers in Immunology, 2026)
BackgroundDiabetes-associated cognitive dysfunction (DACD) is one of the common chronic complications of diabetes mellitus in the central nervous system. Given that current therapeutic agents are limited, exploring novel therapeutic agents is particularly important. The novel IDO-1 inhibitor 3–047 and icaritin (ICT) demonstrate efficacy in ameliorating neuroinflammation and cognitive dysfunction, and their combination exhibits certain hypoglycemic effects. However, the impact of this combination therapy on DACD remains unclear.MethodsThe db/m mice were used as the control group, and the db/db mice were divided into the model group, the combined low-dose group, the combined medium-dose group, the combined high-dose group, and the metformin group. Drug treatment was administered for 16 weeks. Blood glucose, body weight and homeostatic model assessment of insulin resistance were detected as the basic indexes. The Morris water maze was used to evaluate the spatial learning and memory ability of mice. Neuronal damage, apoptosis and degeneration were observed by H&E staining, Nissl staining, TUNEL staining and Fluoro-Jade C staining. Additionally, ultrastructural changes of the hippocampus were observed by transmission electron microscopy. Serum inflammatory factors expression was detected via ELISA, while microglial expression was assessed by immunofluorescence. Protein expression related to the TLR4/MyD88/NF-κB pathway, neuroinflammation, cognitive impairment, synaptic damage, and neuronal apoptosis was analyzed through Western blotting.ResultsCombined therapy with 3–047 and ICT not only improved spatial learning and memory deficits in db/db mice but also modulated the expression of proteins associated with cognitive dysfunction. It inhibited neuronal apoptosis and degeneration, alleviated hippocampal ultrastructural damage, and simultaneously reduced the expression of TLR4/MyD88/NF-κB-related proteins and the occurrence of neuroinflammation.Conclusion3–047 combined with ICT reduces neuronal apoptosis and neuroinflammation and improves cognitive dysfunction in diabetic mice, and these effects are potentially associated with downregulation of the TLR4/MyD88/NF-κB pathway.